Suspension of Mitotic Activity in Dentate Gyrus of the Hibernating Ground Squirrel - Victor I. Popov; Igor V. Kraev; Dmitri A. Ignat'ev; Michael G. Stewart (Neural Plasticity)
Neurogenesis occurs in the adult mammalian hippocampus, a region of the brain important for learning and memory. Hibernation in Siberian ground squirrels provides a natural model to study mitosis as the rapid fall in body temperature in 24 h (from 35-36°C to +4–6°C) permits accumulation of mitotic cells at different stages of the cell cycle. Histological methods used to study adult neurogenesis are limited largely to fixed tissue, and the mitotic state elucidated depends on the specific phase of mitosis at the time of day. However, using an immunohistochemical study of doublecortin (DCX) and BrdU-labelled neurons, we demonstrate that the dentate gyrus of the ground squirrel hippocampus contains a population of immature cells which appear to possess mitotic activity. Our data suggest that doublecortin-labelled immature cells exist in a mitotic state and may represent a renewable pool for generation of new neurons within the dentate gyrus.